Nutrition and bariatric surgery - Kushner, Robert F., 1953-; Still, Christopher D. (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'While bariatric surgery can lead to positive effects, it can also result in increased risk for nutrient malabsorption, deficiency, and clinical complications. This book addresses the dietary and nutritional care of the bariatric surgery patient. It explores the physiological changes that underlie selective nutrient malabsorption, preoperative nutritional assessment and dietary care of the patient through the surgery process, and nutritional clinical complications manifesting in anemia, neurological disorders, metabolic bone disease, and protein-calorie malnutrition. It also covers special populations, including adolescents and pregnant and lactating patients'--
hapter 1. Review of nutritional gastrointestinal physiology imposed by bariatric surgical procedures / Michael A. Via and Jeffrey I. Mechanick -- chapter 2. Nutritional assessment of the bariatric surgery patient / Maria L. Collazo-Clavell -- chapter 3. Nutrition management, pre- and postsurgery / Sue Cummings -- chapter 4. Anemia and bariatric surgery / Mark A. Marinella -- chapter 5. Metabolic bone disease following bariatric surgery / Stephanie F. Deivert and Christopher D. Still -- chapter 6. Neurological disorders / Neeraj Kumar -- chapter 7. Selected nutritional deficiencies (Zinc, Selenium, Vitamins A, D, E, and K, and Niacin) / Yaniv Cozacov, Hira Ahmad, and Raul J. Rosenthal -- chapter 8. Pharmacology of drugs and nutritional supplements / Margaret Malone -- chapter 9. Macronutrient concerns : protein-energy malnutrition / Pornpoj Pramyothin and Caroline M. Apovian -- chapter 10. Special populations : adolescents / Kathleen B. Hrovat, Linda M. Kollar, and Thomas H. Inge -- chapter 11. Special populations : pregnancy and lactation after bariatric surgery/ Michelle A. Kominiarek -- chapter 12. Psychological issues and eating behavior before and after bariatric surgery / David B. Sarwer and Rebecca J. Dilks -- chapter 13. Nutrition and body contouring procedures / Siamak Agha-Mohammadi -- chapter 14. Obesity in critical illness : implications for nutrition therapy / Stephen A. McClave, Thomas H. Frazier, Samir D. Vermani, and Ryan T. Hurt -- chapter 15. Nutrition and weight regain in the bariatric surgical patient / Kirsten Webb Sorensen, Holly Herrington, and Robert F. Kushner.
Includes bibliographical references and index.
Keywords: Bariatric Surgery -- rehabilitation; Nutrition Disorders -- prevention & control; Feeding behavior -- Physiology; Postoperative Complications -- prevention & control